2022
DOI: 10.22541/au.165398225.50426806/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“All-on-4” and “All-on-6” Treatment Concept Applied Using Computer-Guided Surgery in a Patient: Case Report with a 2-Years Follow-up

Abstract: Computer software was used for implant planning and guided surgery. A provisional prosthesis was loaded on the day of surgery; the definitive prosthesis with a milled titanium framework was loaded one year later. There were no clinical or radiographic changes around the dental implants at two-years post- surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, most studies are case reports (Bolding & Reebye, 2022; Mozer, 2020), compare previous findings with a small sample size (Chen, Al‐Taezi, et al., 2023; Yang et al., 2023) or are in vitro studies (Chen, Bai, et al., 2023; Tao et al., 2022), in which the clinical factors cannot be completely reproduced or calculated, such as jaw tremors, saliva and bleeding, limited mouth opening and real bone reaction to the surgery (Bai et al., 2021; Parra‐Tresserra et al., 2021). Studies have shown that implant accuracy in in vivo trials is lower than in in vitro and ex vivo models, especially in apical global and axial deviations (Albaqawi, 2023; Bover‐Ramos et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most studies are case reports (Bolding & Reebye, 2022; Mozer, 2020), compare previous findings with a small sample size (Chen, Al‐Taezi, et al., 2023; Yang et al., 2023) or are in vitro studies (Chen, Bai, et al., 2023; Tao et al., 2022), in which the clinical factors cannot be completely reproduced or calculated, such as jaw tremors, saliva and bleeding, limited mouth opening and real bone reaction to the surgery (Bai et al., 2021; Parra‐Tresserra et al., 2021). Studies have shown that implant accuracy in in vivo trials is lower than in in vitro and ex vivo models, especially in apical global and axial deviations (Albaqawi, 2023; Bover‐Ramos et al., 2018).…”
Section: Introductionmentioning
confidence: 99%